Effect of Environmental Conditions on the Yield of Peel and Composition of Essential Oils from Citrus Cultivated in Bahia (Brazil) and Corsica (France) - François Luro; Claudia Garcia Neves; Gilles Costantino; Abelmon da Silva Gesteira; Mathieu Paoli; Patrick Ollitrault; Félix Tomi; Fabienne Micheli; Marc Gibernau (Agronomy, 2020)
The cosmetic and fragrance industry largely exploits citrus essential oils (EOs) because of their aromatic properties. EO compositions are complex and differ between fruit pericarp (PEO) and leaf (LEO). Citrus fruit grow in many countries under very different climates. Seventeen citrus cultivars were selected and their similarities between the two collections were verified by SSR (Single Sequence Repeat) and InDel (Insertion and Deletion) markers to assess the effects of the environment and cultivation practices on the EO yield and composition. LEOs and PEOs were extracted by water distillation and analyzed by GC-MS. PEO yields were generally higher in Corsica than in Bahia, especially in the citron family. PEOs in this family were richer in limonene in Bahia than in Corsica while, conversely, neral, geranial and derivatives were present in a higher proportion in Corsican varieties. A few minor components were site-specific, such as nookaton, a pummelo-specific compound that was not present in grapefruit cultivated in Bahia. If climate change over the last 20 years has not affected the PEO composition in Corsica, the contrasted environmental conditions and cultural practices between Bahia and Corsica could possibly explain the EO variations.